Fluorescent supramolecular hydrogels self-assembled from tetraphenylethene (TPE)/single amino acid conjugates. Issue 37 (8th June 2018) - Chu, Nien-Tzu; Chakravarthy, Rajan Deepan; Shih, Nai-Chia; Lin, Yen-Hsu; Liu, Yen-Chu; Lin, Jhong-Hua; Lin, Hsin-Chieh
Abstract : TPE-Ser molecules exhibit non-covalent interactions necessary for hydrogelation under physiological pH conditions. Abstract : Herein, we report the synthesis of simple TPE/single amino acid conjugates, TPE-Ser andTPE-Asp with side-chains featuring functional groups that may provide an additional hydrogen bonding network for hydrogelation in aqueous medium.TPE-Ser, which has the lowest molecular weight, containing hydroxyl groups undergoes self-assembly into supramolecular hydrogels under physiological pH conditions.TPE-Asp with a carboxylic group side chain undergoes the self-assembly and hydrogelation processes under slightly acidic conditions (pH = 6.0). UV-vis, IR, PL and rheological studies clearly indicate the formation, stability and fluorescence properties of TPE-amino acid hydrogels. TEM micrographs of the hydrogels indicate that the compounds are self-assembled into a nanosheet morphology with random size and shape. Further, in vitro analysis ofTPE-Ser andTPE-Asp with 3A6 cells shows that the compounds exhibit unique fluorescence signals in microcellular environments thus making them suitable candidates for bioimaging applications. Overall, these findings highlight the importance of the structure-hydrogelation relationship and provide new insights into the design of single amino-acid-based supramolecular hydrogels.